Reverse Shoulder Arthroplasty After Prior Rotator Cuff Repair: A Matched Cohort Analysis. Issue 3 (1st February 2022) - Marigi, Erick M.; Tams, Carl; King, Joseph J.; Crowe, Matthew M.; Werthel, Jean-David; Eichinger, Josef; Wright, Thomas; Friedman, Richard J.; Schoch, Bradley S.
Abstract : Introduction: Rotator cuff repair (RCR) is commonly performed before reverse shoulder arthroplasty (RSA) with conflicting evidence on the effect on arthroplasty outcomes. The purpose of this investigation was to evaluate the effect of a prior RCR on the outcomes and complications of primary RSA. Methods: Between 2007 and 2017, 438 RSAs performed in patients with a prior RCR and 876 case-matched controls were identified from a multicenter database. Patients were grouped based on a preoperative diagnosis of glenohumeral osteoarthritis (GHOA) and rotator cuff tear arthropathy (CTA). Data collected included range of motion, strength, complications, and revisions. Additional clinical metrics included American Shoulder and Elbow Society score, Constant score, Shoulder Pain and Disability Index, Simple Shoulder Test, and the University of California Los Angeles shoulder score. Results: Compared with controls, both GHOA and CTA study groups demonstrated lower postoperative forward elevation (FE) (133° versus 147°, P < 0.001; 133° versus 139°, P = 0.048) and FE trength (6.5 versus 8.2, P = 0.004; 6.1 versus 7.3, P = 0.014). In addition, inferior improvements were observed in the GHOA and CTA study groups with respect to abduction (38° versus 52°, P = 0.001; 36° versus 49°, P = 0.001), FE (41° versus 60°, P < 0.001; 38° versus 52°, P = 0.001), ER (16° versus 25°, P < 0.001; 10° versus 17°, P = 0.001), and Constant score (28.4 versus 37.1, P < 0.001; 26.2 versus 30.9, P = 0.016). Compared with controls, no differences were observed in the GHOA and CTA study groups with respect to notching (11.2% versus 5.6%, P = 0.115; 5.8% versus 7.9%, P = 0.967), complications (4.3% versus 1.6%, P = 0.073; 2.5% versus 2.7%, P = 0.878), and revision surgery (3.1% versus 0.9%, P = 0.089; 1.1% versus 1.3%, P = 0.822). Conclusion: RSA after a prior RCR improves both pain and function, without increasing scapular notching, complications, or revision surgery. However, compared with patients without a prior RCR, postoperative shoulder function may be slightly decreased. Level of Evidence: III; Retrospective Cohort Study.